Do neighbours matter? The effect of single- and mixed-species sowing density on seed germination of annual wetland plants - Bao, Francielli [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Pott, Arnildo; Elsey-Quirk, Tracy; de Assis, Marco Antonio [UNESP]; Arruda, Rafael; Ramos, Desirée Marques [UNESP] (Wiley, 2021)
Question: Germination is one of the decisive processes influencing species presence and plant community structure. Here, we investigated the influence of seed density and single and mixed species on germination percentage and timing using annual wetland plants of the Pantanal in Brazil. Location: Seeds were collected from annual species occupying a seasonally flooded grassland, at Fazenda São Bento (19°29′27,3″ S; 57°01′55,9″ W), in the Abobral sub-region, Pantanal, Mato Grosso do Sul (Central-West Brazil). Methods: Experiments on the effects of seed density dependence on the germination time in intraspecific (single-species) and interspecific (mixed-species) treatments were conducted with ten annual species at three levels: for intraspecific — scarce (one seed), moderate (10 seeds), and high (20 seeds); and for interspecific — low (one each), medium (10) and abundant (20). Results: The germination percentage was independent of density and species mixtures. Germination time was density-dependent for the mixed-species treatment, but not the single-species treatments. Six species had a shorter germination time, suggesting a group priority effect. Other species delayed or did not alter their germination time, indicating that the response to intraspecific seed densities is species-specific. Conclusion: These findings illustrate that even though species have a history of coexistence and characteristics of rapid germination, seeds can alter germination time if they perceive neighbouring seeds of other species. Species that respond with a faster germination time may have a competitive advantage for recruitment and growth. These terrestrial species show high initial colonization power, which is essential in the regeneration of wetlands after flood disturbance.
Keywords: annual seeds; coexistence; colonization strategies; germination time; percentage of germination; priority effect